Hatching Failure in Wood Turtles (Glyptemys insculpta) Is Linked to Maternal Identity - Duchak, Thomas J.; Burke, Russell L. (Frontiers in Ecology and Evolution, 2022)
Wood turtles (Glyptemys insculpta) have been suffering range-wide population declines since the 1900s. Most monitoring efforts of these turtles involve population surveys to assess population size and viability but relatively few investigate rates of reproductive success. We collected four consecutive years (2013 – 2016) of wood turtle nesting data at a nesting site in northwestern New Jersey; population-level hatching success was unusually low. Furthermore, annual, intra-individual hatch rates and comparisons between natural and artificial incubation revealed that approximately half of all females usually produced clutches with low (<50%) hatch rates, regardless of incubation conditions. In contrast, the annual hatch rates of other females were either consistently high (>50%) or highly variable, ranging from 0 – 100%. Thus, some adult females are potentially making much larger contributions to the next generation than others. A repeatability analysis suggested that approximately 60% of the hatch rate variability observed in this population can be attributed to maternal identity. The remaining 40% may be attributed to the random environmental factors that are often theorized to be potential reasons for reduced hatch rates in turtle populations (e.g., unsuitable incubation conditions, flooding, desiccation, egg infertility, egg damage due to improper handling by researchers, root and insect predation, and microbial infection). The ultimate causes of this population’s hatching success variability are uncertain, but maternally-linked hatching failure in turtle populations could be associated with inbreeding, infertility, senescence, inadequate maternal diets, or environmental contamination. This study indicates that commonly suggested hypotheses for hatching failure, such as unsuitable incubation conditions or infertility, are unlikely to explain all of the hatch rate variability in some turtle populations. This study also reveals a cryptic conservation implication for vulnerable turtle populations: that the presence of many nesting females and nests does not necessarily assure high or even sustainable reproductive rates. When coupled with the high rates of nest predation and low juvenile survival rates that are common in most turtle populations, the exceedingly low hatch rates observed in this population suggest that recruitment in some turtle populations could be severely hindered even when nests are protected in the field or incubated in laboratory settings.